WEWENANG MAHKAMAH KONSTITUSI DALAM PENGUJIAN UNDANG-UNDANG HASIL RATIFIKASI PERJANJIAN INTERNASIONAL YANG BERSIFAT MULTILATERAL (STUDI KASUS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 33/PUU-IX/2011) - Ni Ketut Aprilyawathi (Yuridika, 2015)
Indonesia is one of the founder of ASEAN in Bangkok, Thailand. After ASEAN Charter being made I 2007. 1 year later, Indonesia already ratificate that international agreement with National regulation which is Undang-Undang Nomor 38 Tahun 2008. After this kind of action some citizen especially who works in goods trade on a small scale, feel lost because the effect of this ratification. Based on that reason, some citizen make appeal on Constituional Court. Constitutional Court has authority to review Undang-Undang based on UUD NRI 1945. But this kind of review is not the same as the one which regulate on constitutional. Undang-Undang which being made together by parlement and President its not the same as Undang-Undang which being made to ratificate a international agreement. In making a generally Undang-Undang, it needs approval from the both parlement and President and the idea to make a new undang-undang it can based on both of them. Its different in making Undang-Undang ratification for international agreement, President obviously has a bigger role than parlement. The idea to ratificate international agreement, always based on Presiden idea and parlement just has authority to approving and decline the idea. Approving a Undang-Undang for ratificate an international agreement is not an parlemen’s action as legulator but as a state body that doing a check and balances role. On Putusan MK no. 33/PUU-IX/2011, it says that constitutional body has authority to adjudicate this case and decline all of the pleading. Issues about power of binding between Indonesia and international agreement having no problem cause constitutional court says  “decline all of the pleading”, but it be a problem when the Constitutional Court says they have the authority to prejudice the case.